Sap flow technique as a tool for irrigation schedule in grapevines: control of the plant physiological status - Pons P.J.; Truyols M.; Flexas J.; Cifre J.; Medrano H.; Ribas-Carbó M. (Drought management: scientific and technological innovations, 2008)
The main goal of our research has been to obtain precise parameters based on sap flow techniques that allow to maintain grapevine water status under a sustained moderate water stress. Based on previous work of our group, we have used stomatal conductance (gs) as a parameter that indicates the physiological status of the plant (Flexas and Medrano, 2002). A good correlation between stomatal conductance and the slope of the afternoon sap flow decline has been determined. This Sap Flow Afternoon Decline (SFAD) has been used to determine the irrigation schedule of grapevines (Vitis vinifera L. cv Tempranillo) based only on sap flow measurements but considering the physiological status of the plant. We propose that SFAD can be easily computerized and applied to grapevine irrigation.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)